STUDENTS’ PERCEPTIONS FOR THE CHEMISTRY LABORATORY ENVIRONMENT IMPROVEMENT - Yuli Rahmawati; Rekha Koul (Jurnal Riset Pendidikan Kimia (JRPK), 2011)
Chemistry students’ perceptions of the chemistry laboratory learning environment were investigated in Jakarta State University. An already existing instrument Chemistry Laboratory Environment Inventory (CLEI) questionnaire was translated into Bahasa Indonesia and administered to 410 university students in three different years of chemistry study. Data analyses supported the validity and reliability of the instrument when used in this context and there were no statistically significant differences in mean scores for gender and programme of study. However, the mean differences in students’ perceptions of their laboratory environment were statistically significant by year level. These differences were further validated by the interview data. Qualitative data were obtained from laboratory observations and interviews with the students. Furthermore, both quantitative and qualitative data confirmed that students wished for an improved laboratory learning environment in terms of more opportunities to explore their own interests and to work with better laboratory equipment. The chemistry department staff could use the information from this study to guide them in making changes for improving the learning process in the laboratory.